Adherence to a digital therapeutic mediates the relationship between momentary self-regulation and health risk behaviors - Plaitano, Enzo G.; McNeish, Daniel; Bartels, Sophia M.; Bell, Kathleen; Dallery, Jesse; Grabinski, Michael; Kiernan, Michaela; Lavoie, Hannah A.; Lemley, Shea M.; Lowe, Michael R.; MacKinnon, David P.; Metcalf, Stephen A.; et al. (Frontiers in Digital Health, 2025)
IntroductionSmoking, obesity, and insufficient physical activity are modifiable health risk behaviors. Self-regulation is one fundamental behavior change mechanism often incorporated within digital therapeutics as it varies momentarily across time and contexts and may play a causal role in improving these health behaviors. However, the role of momentary self-regulation in achieving behavior change has been infrequently examined. Using a novel momentary self-regulation scale, this study examined how targeting self-regulation through a digital therapeutic impacts adherence to the therapeutic and two different health risk behavioral outcomes.MethodsThis prospective interventional study included momentary data for 28 days from 50 participants with obesity and binge eating disorder and 50 participants who smoked regularly. An evidence-based digital therapeutic, called Laddr™, provided self-regulation behavior change tools. Participants reported on their momentary self-regulation via ecological momentary assessments and health risk behaviors were measured as steps taken from a physical activity tracker and breathalyzed carbon monoxide. Medical regimen adherence was assessed as daily Laddr usage. Bayesian dynamic mediation models were used to examine moment-to-moment mediation effects between momentary self-regulation subscales, medical regimen adherence, and behavioral outcomes.ResultsIn the binge eating disorder sample, the perseverance [β1 = 0.17, 95% CI = (0.06, 0.45)] and emotion regulation [β1 = 0.12, 95% CI = (0.03, 0.27)] targets of momentary self-regulation positively predicted Laddr adherence on the following day, and higher Laddr adherence was subsequently a positive predictor of steps taken the same day for both perseverance [β2 = 0.335, 95% CI = (0.030, 0.717)] and emotion regulation [β2 = 0.389, 95% CI = (0.080, 0.738)]. In the smoking sample, the perseverance target of momentary self-regulation positively predicted Laddr adherence on the following day [β = 0.91, 95% CI = (0.60, 1.24)]. However, higher Laddr adherence was not a predictor of CO values on the same day [β2 = −0.09, 95% CI = (−0.24, 0.09)].ConclusionsThis study provides evidence that a digital therapeutic targeting self-regulation can modify the relationships between momentary self-regulation, medical regimen adherence, and behavioral health outcomes. Together, this work demonstrated the ability to digitally assess the transdiagnostic mediating effect of momentary self-regulation on medical regimen adherence and pro-health behavioral outcomes. Clinical Trial RegistrationClinicalTrials.gov, identifier (NCT03774433).